Effect of Electro-Sprayed Porous Electrodes on the Performance and Stability of Water Electrolysis - Lee, Jong Yoon; Park, Hee-Young; Hwang, Sang Youp; Lee, Gi Won; Park, Gwan Gyu; Hupp, Joseph T.; Jang, Jong Hyun; Joh, Han-Ik (American Chemical Society, 2025)
The efficiency of proton exchange membrane water electrolysis (PEMWE) is a critical issue in realizing the production of green hydrogen. The coexistence of three phases in the catalyst layer of PEMWE causes mass transport limitation at the interfaces between them. In particular, the vigorous production of gaseous hydrogen and oxygen derived from liquid water is generated in the form of bubbles that seriously deactivate the membrane electrode assembly (MEA). In this study, we investigated the effect of porous structure in the electrode on the efficiency of hydrogen production at a high current density, which is highly related to the mass transport limitation. A widely used commercial catalyst (IrO2) was directly coated on the membrane by the electro-spray method. Porous electrodes on the membrane were formed by the charged catalyst particles that repulsed each other due to their electrostatic forces. Our membrane electrode assembly (MEA) exhibited outstanding electrolysis performances such as 5.3 A cm-2 and 3.2 A cm-2 at 2.0 and 1.8 V, respectively, which are the highest values compared with the results published in the current studies. In addition to porosity, it was confirmed that optimum binder contents positively affect the hydrophobicity and contact resistance of MEA. Through a simple porosity-controlled technique, the performance of PEMWE, in which three phases coexist, can be improved by more than 60 %. Accordingly, we expect that our systematic study on the role of porosity in the electrodes opens a new era to efficiently produce green hydrogen.